Testicular Dirofilariasis in an Italian 11-Year-old Child. Issue 12 (8th September 2022) - Pansini, Andrea; Magenes, Vittoria Carlotta; Casini, Francesca; Guida, Gabriella; De Sanctis, Marina; Canonica, Carlotta Paola Maria; Rossi, Roberta Simona; Zuccotti, Gianvincenzo; Giacomet, Vania
Abstract : Dirofilariasis is a rare infection caused by a vector-borne nematode that can be accidentally transmitted to humans. We report a case of a 11-year-old child with a painless scrotal cyst caused by Dirofilaria repens, initially suspected by ultrasound scan and then confirmed by histopathologic examination.